Tc-99m DTPA Perfusion Scintigraphy and Color Coded Duplex Sonography in the Evaluation of Minimal Renal Allograft Perfusion - Bair, H.-J.; Günter, E.; Rupprecht, H.; Platsch, G.; Becker, D.; Neumayer, H.-H.; Wolf, F. (Nuklearmedizin - NuclearMedicine, 1997)
Aim: The clinical impact of perfusion scintigraphy versus color coded Duplex sonography was evaluated, with respect to their potential in assessing minimal allograft perfusion in vitally threatened kidney transplants, i.e. oligoanuric allografts suspected to have either severe rejection or thrombosis of the renal vein or artery. Methods: From July 1990 to August 1994 the grafts of 15 out of a total of 315 patients were vitally threatened. Technetium-99m DTPA scintigraphy and color coded Duplex sonography were performed in all patients. For scintigraphic evaluation of transplant perfusion analog scans up to 60 min postinjection, and time-activity curves over the first 60 sec after injection of 370-440 MBq Tc-99m diethylenetriaminepentaacetate acid (DTPA) were used and classified by a perfusion score, the time between renal and iliac artery peaks (TDiff) and the washout of the renogram curve. Additionally, evaluation of excretion function and assessment of vascular or urinary leaks were performed. By color coded Duplex sonography the perfusion in all sections of the graft as well as the vascular anastomoses were examined and the maximal blood flow velocity (Vmax) and the resistive index (Rl) in the renal artery were determined by means of the pulsed Doppler device. Pathologic-anatomical diagnosis was achieved by either biopsy or post-explant histology in all grafts. Results: Scintigraphy and color coded Duplex sonography could reliably differentiate minimal (8/15) and not perfused (7/15) renal allografts. The results were confirmed either by angiography in digital subtraction technique (DSA) or the clinical follow up. Conclusion: In summary, perfusion scintigraphy and color coded Duplex sonography are comparable modalities to assess kidney graft perfusion. In clinical practice scintigraphy and color-coded Doppler sonography can replace digital subtraction angiography in the evaluation of minimal allograft perfusion.
Keywords: Renal transplant perfusion scintigraphy; color coded duplex sonography; vitally threatened kidney transplants